Mobile Learning Perception and Interest among Higher Education Distance Learners in Asia - Arafeh, Karimi; Nurziyanti, Mohamad Khan; Yusup, Hashim (2010)
This study, as a part of Asia e University mobile Learning project (AeUmL), aimed to investigate the higher education distance learners’ conceptualization and the level of interest towards having the opportunity to learn while mobile. It also addressed participants’ access level and frequency use of the technologies typically employed in mobile learning. Quantitative data were collected from 112 survey respondents enrolled in AeU Post Graduate Programs in Kuala Lumpur center. Results yielded a mixed response in terms of student perception on various examples of mobile learning while their interest level and attitudes towards having the option of mobile learning were reported very high. Students’ participation rate in utilizing mobile technologies and electronic learning activities were analyzed. Future research implications and issues surrounding the development of mobile learning in Asian higher education are also discussed.